Unusual complications after dental extractions: a narrative review - Orellano-Rudas, Álvaro; Morales-Lizcano, Karenmy; Castro-Núñez, Jaime (Revista Facultad de Odontología Universidad de Antioquia, 2022)
Dental extraction is one of the most common and most frequent surgical procedures performed by oral and maxillofacial surgeons. This surgical procedure is carried out in a controlled environment that ensures success in most cases. However, unexpected complications with a high risk of causing temporary or permanent disabling injuries may develop. This review focuses on rare complications that can occur when performing dental extractions. In order to fulfill the purpose of this review, a literature search was carried out in different databases; 34 articles reporting rare complications were selected, all were case reports. It was found that the most reported unusual complications after dental extraction were spinal epidural abscess and emphysema. Low mortality associated with these complications was also observed. Similarly, there are currently few publications on unusual complications as a result of tooth extraction. These rare complications should be reported more frequently in order to expand our Knowledge and to establish care protocols